The Role of Civil Society Organizations in Improving the Level of the Educational Process to Achieve Sustainable Development in Light of the State›s Vision for 2030: An Applied Study on Community Associations - Shedid, Mustafa (The Arab Journal of Administration, 2022)
Community associations are part of civil society organizations inside the country and have a historical extension for a long time. In Egypt, the axis of sustainable development is considered one of the most important directions of civil society’s activity in general and community associations in particular, especially in Cairo Governorate. The current study aimed to identify the role of community associations in achieving sustainable development in the education sector according to the strategic vision of the state for 2030 through alphabetical and digital literacy, educational empowerment of students, and improvement of competitiveness in the educational system on the national level. The researcher adopted the descriptive approach in studying the variables of the study and employed the applied analytical approach in knowing the opinions of the surveyors about the role of community associations in achieving sustainable development of the educational process. This study assumed that there is a statistical relationship between the role of community associations as a civil society organization in improving the educational process and the achievement of sustainable development in light of the strategic vision of the state for 2030. By testing the main hypothesis of the study and its sub-hypotheses, the study reached a set of results. The study concluded that there is a strong direct correlation between the sub-variables of the independent variable (activating the role of civil associations, developing the awareness of community associations, and adopting educational strategy by community associations) and the dependent variable (achieving sustainable development in the education sector in accordance with the strategic vision of the state for 2030). The study also reached a set of recommendations. The most important of which is the need to set appropriate strategies to achieve the strategic vision of the State for 2030 within the framework of serious partnership that turns into a societal mandate to manage civil society organizations. The study also recommended that it is necessary to adopt civil society organizations as a partner with the government in setting up serious planning and executive programs for the development process on the local level.